2019
DOI: 10.1111/cdev.13200
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Disaster Impacts on Academic Performance of Primary School Children

Abstract: Social disruption caused by natural disasters often interrupts educational opportunities for children. However, little is known about children's learning in the following years. This study examined change in academic scores for children variably exposed to a major bushfire in Australia. Comparisons were made between children attending high, medium, and low disaster‐affected primary schools 2–4 years after the disaster (n = 24,642; 9–12 years). The results showed that in reading and numeracy expected gains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 56 publications
2
90
1
4
Order By: Relevance
“…It is possible that there is a delayed academic achievementpsychological distress relationship among disaster-exposed students. For example, higher exposure to the Black Saturday bushfires in Australia was found to impact on academic performance four years after the fires (Gibbs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that there is a delayed academic achievementpsychological distress relationship among disaster-exposed students. For example, higher exposure to the Black Saturday bushfires in Australia was found to impact on academic performance four years after the fires (Gibbs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The pre-post methodology separates the current study from the majority of disaster research published to date, which has been limited to utilising post-event measures. Although our measure of mine fire exposure based on school location reflects earlier research (Gibbs et al, 2019), a more objective measure of exposure based on diarised location (home and school) during the event may have improved the capacity to measure exposure-response relationships.…”
Section: Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…The Australian Labor Party recently requested additional trauma counselling for students in bushfire zones when they go back to school. The request was based in part on a 2019 study of 25,000 kids, which found that students exposed to the 2009 Black Saturday Australian bushfires were more likely to fall behind in the classroom (Gibbs et al, 2019;Trounson, 2019). That 2009 fire claimed 173 lives.…”
Section: Australian Bushfires Cause Long-term Mental Health Effectsmentioning
confidence: 99%